Siga os números: introdução ao uso de dados no jornalismo de finanças e negócios - Segala, Mariana (2017)
This final report from the interdisciplinary professional master in Technologies, Comunication and Education of Federal University of Uberlândia presents the development of a handbook, published as an e-book, about the use of techniques, practices and tools of data journalism in the journalistic coverage of economy, entitled Follow the Numbers: Introduction to Data Use in Business and Financial Journalism. Data journalism, that became a trend in newsrooms during the past decade, emerges from the technical, social and institutional implications from the advent of networks. It reflects the growth of citizen’s access to databases, the global movement asking for transparency and the dissemination of softwares and applications for data analysis and visualization. Specialization area traditionally associated with number manipulation, business journalism can make use of data journalism instruments to improve its products. Considering the current economic coverage direction towards subjects regarding financial markets and corporate performance, Follow the Numbers tries to guide journalism students and journalists not familiar with data journalism and/or business journalism about where to find, how to get and what to do with data in business and financial journalistic investigations.